1992
DOI: 10.1002/pssa.2211330236
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Properties of Tm3+ in Y3Al5O12 in the Near UV and Visible Ranges

Abstract: For the first time the emission properties of Tm3+ doped Y3Al5O12 are studied in the near UV and visible ranges at 4.2 and 295 K. The observed emission peaks are ascribed to the transitions between Tm3+ energy levels and an overall energy level scheme of the Tm3+ ion in Y3Al5O12 with radiative and nonradiative transitions in UV and visible ranges is proposed. The reabsorption and cross‐relaxation processes are suggested as a possible reason for the observed nonexponential decay originating mainly from the 1G4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
11
1
1
Order By: Relevance
“…With the distance between ions fixed in the crystal, the average value for R ¼ 50 ( A; estimated from the position of the substitution of Tm 3þ for Sr 2þ in the unit cell and scaled by the number of unit cells required for a 0:21 at% concentration. The cross-relaxation rates at this concentrations ranged from 11 to 81 s À1 ; where the rate is increasing with increasing temperature from 10 to 200 K: This experimentally determined rate is much smaller than was previously observed for Tm 3þ in Y 3 Al 5 O 12 [14]. The rates observed in this report are low primarily because of the low Tm 3þ concentration.…”
contrasting
confidence: 64%
See 2 more Smart Citations
“…With the distance between ions fixed in the crystal, the average value for R ¼ 50 ( A; estimated from the position of the substitution of Tm 3þ for Sr 2þ in the unit cell and scaled by the number of unit cells required for a 0:21 at% concentration. The cross-relaxation rates at this concentrations ranged from 11 to 81 s À1 ; where the rate is increasing with increasing temperature from 10 to 200 K: This experimentally determined rate is much smaller than was previously observed for Tm 3þ in Y 3 Al 5 O 12 [14]. The rates observed in this report are low primarily because of the low Tm 3þ concentration.…”
contrasting
confidence: 64%
“…While there have been a number of studies of the temperature dependence of the cross-relaxation process in Tm 3þ or other lanthanide-doped dielectric crystals, most of these prior studies have reported the temperature-dependent emission process as the sum of two or more exponential processes [8,9,14]. This is the case for prior reports of the emission decay of Tm 3þ by Gruber et al [25].…”
Section: Article In Pressmentioning
confidence: 87%
See 1 more Smart Citation
“…According to the result reported by Thomas et al, the absorption transition 3 H 6 → 1 G 4 was exactly located at 460 nm. However, Mares et al indicated the transition occurring at 481 nm. Our calculated wavelength of the transition from 1 G 4 → 3 H 6 is equal to 477 nm, which suggests a slightly better agreement with Mares et al The transitions at 364, 455, and 511 nm are assigned to 1 D 2 → 3 H 6 , 1 D 2 → 3 F 4 , and 1 I 6 → 3 F 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The emission in this region is an important requirement for a possible application of these compounds as detectors of ionizing radiation [3]. Mares et al [11], for instance, observed weak blue emission as well as stronger peaks at 650 and 675 nm for a YAG crystal doped with 0.76% Tm at 4.2 K. So, Lopez et al [6] tried to enhance blue emission in Tm-doped Y 3 Al 5 O 12 (YAG) crystal by co-doping with lithium, and as a result the blue emission was increased by 87%, and red and IR ones also increased, but to a lesser extent. Therefore, the lutetium or yttrium aluminates prepared in this work are good host lattices for Tm because no red emission is observed and the intensity of the blue one is high.…”
Section: Resultsmentioning
confidence: 99%